AL-SHIRĀ’ AL-‘AQADĪ AL-WUJŪDĪ FĪ NUSANTARA FĪ AL-QARN AL-SĀBI’ ‘ASYARA AL-MĪLĀDĪ - Basyir Arif (Ushuluna: Jurnal Ilmu Ushuluddin, 2021)
This paper discusses the history of Islamic thought in Nusantara. The focus of discussion is on ideology conflict of wujudiyyah by Hamzah Fansuri and which were refufed by Nuruddin ar-Raniri and Abdurrauf singkil. Hamzah Fansuri was considered as a scholar who transmit Wujudiyyah in Nusantara in 17th century. Followed by his student Syamsuddin as-Sumatrani as his position as influencer of Wujudiyyah which causes debates and disputes in Islamic theology. Raniri who had lived after Fansuri and Sumatrani, he had ordered to fighted and considered their followers to be infidels; then Abdurrauf singkil was approach to a moderat dialogue between opposite opinions.